Pengaruh Resiko Kredit terhadap Profitabilitas dengan likuiditas sebagai Mediasi - Rizky Fitroh Hamdani; Irma Indira (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
This study aimed to analyze the effect of credit risk on profitability with liquidity as a mediating variable in banking companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The study employed a quantitative approach with an explanatory research design. Secondary data were obtained from annual financial statements, and the sample consisted of 31 banking companies selected through purposive sampling from a total of 47 companies. The research variables included credit risk as the independent variable, profitability proxied by Return on Assets (ROA) as the dependent variable, and liquidity proxied by the Loan to Deposit Ratio (LDR) as the mediating variable. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through the assessment of the measurement model and the structural model. The results indicated that credit risk did not affect profitability and did not affect liquidity, while liquidity affected profitability. The findings also demonstrated that liquidity did not mediate the relationship between credit risk and profitability. The study implied that liquidity management played an important role in supporting bank profitability, whereas the influence of credit risk on profitability during the study period was likely driven by other factors outside the proposed model. This study provided empirical evidence on banking performance dynamics in 2022–2024; however, generalization should have been made cautiously due to the limited observation period and the variables included.